Analysis of Sharia Economic Development in the Era of Globalization in Indonesia: Opportunities & Challenges - Herlina Angganita, Nurul Aulia; Novitasari, Evi Fitria (Universitas Gorontalo, 2024)
Sharia economics has become a topic that has attracted attention in the development of the global economy, especially in the current era of globalization. This article highlights basic principles such as monotheism, balance, benefit, taawun, and justice in the context of sharia economics, taking into account the prohibitions on usury, maysir, and gharar. The research was carried out through a qualitative descriptive approach using library research methods. This article also discusses the history and development of sharia economics in Indonesia, including the challenges faced and the government's efforts to develop it. This article emphasizes the importance of developing sharia economics as a relevant alternative in achieving sustainable and equitable development.